Endothelial-to-mesenchymal transition: An underappreciated mediator of diabetic complications - Wang, Eric; Wang, Honglin; Chakrabarti, Subrata (Frontiers in Endocrinology, 2023)
Diabetes and its complications represent a great burden on the global healthcare system. Diabetic complications are fundamentally diseases of the vasculature, with endothelial cells being the centerpiece of early hyperglycemia-induced changes. Endothelial-to-mesenchymal transition is a tightly regulated process that results in endothelial cells losing endothelial characteristics and developing mesenchymal traits. Although endothelial-to-mesenchymal transition has been found to occur within most of the major complications of diabetes, it has not been a major focus or study or a common target in the treatment or prevention of diabetic complications. In this review we summarize the importance of endothelial-to-mesenchymal transition in each major diabetic complication, examine specific mechanisms at play, and highlight potential mechanisms to prevent endothelial-to-mesenchymal transition in each of the major chronic complications of diabetes.